Karakteristik Organoleptik dan Masa Simpan Biskuit Fortifikasi Tepung Ikan Cakalang serta Ekstrak Cangkang Telur Ayam - Rosnah, Rosnah; Imanuddin, Imanuddin; Kusumawati, Evi; Fathurrahman, Teguh; Adam, Adriani (PT Karya Inovasi Berkelanjutan, 2025)
Introduction and MethodsSkipjack tuna is a food ingredient that serves as a source of animal protein, rich in essential amino acids, essential fatty acids, taurine, vitamins, and minerals, but it has not been widely utilized. Similarly, chicken eggshells, which are a source of calcium, have also not been fully utilized. To increase their value and benefits, both ingredients were processed into flour for the fortification of biscuits, which are snacks favored by the community. This study aimed to analyze the organoleptic characteristics, chemical composition, and shelf life of biscuits fortified with skipjack tuna flour and chicken eggshell extract as an alternative supplementary food for adolescent girls with anemia. This research was experimental, using a Completely Randomized Design (CRD) with proportions of skipjack tuna flour and chicken eggshell extract, conducted in duplicate. The treatments included F0 (without the addition of skipjack tuna flour and chicken eggshell extract) as a control, F1 (a combination of 10% skipjack tuna flour and 3% chicken eggshell extract), and F2 (a combination of 15% skipjack tuna flour and 3% chicken eggshell extract). The organoleptic test was conducted with 30 semi-trained panelists. Data were analyzed using SPSS 26 with the Kruskal-Wallis test (α ≤ 0.05). The measurement of the biscuit's chemical composition included levels of carbohydrates, protein, fat, moisture, ash, iron (Fe), calcium (Ca), and vitamin C using AOAC (2005) methods. The biscuit's shelf life was measured using parameters of total microbial count (TMC), moisture content (gravimetric method), and free fatty acid content (alkalimetry titration). The data on chemical content and shelf life parameters were analyzed using ANOVA. ResultsThe results showed that the most preferred biscuit by panelists was F1, with the addition of 10% skipjack tuna flour and 3% chicken eggshell extract. The chemical composition of F1 biscuits per one hundred grams contained 470.66 kcal of energy, 11.47 g of protein, 18.96 g of fat, 63.39 g of carbohydrates, 8.39 mg of iron, 1,523 mg of calcium, and 0.48 mg of vitamin C. The biscuits were yellowish-brown in color, with a distinctive fish aroma and taste, and a crunchy texture. The Total Plate Count after 28 days of storage was 8.4 × 10³ CFU/g. The selected formula in this study was F1, with the addition of 10% skipjack tuna flour and 3% eggshell extract. ConclusionThe best organoleptic characteristics were found in the control, but the biscuit with the addition of 10% skipjack tuna flour and 3% eggshell flour (F1) was also preferred and had higher nutritional value compared to the control biscuit.